Characters in search of a home: a study of themes in the work of David Storey - Howie, Claerwen (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1984)
From Introduction: Anyone familiar with David Storey's work will find, on reading a brief outline of his life, that much of the inspiration for his novels and plays springs from personal experience. The third son of a coal-miner, he was born in Wakefield on 13 July 1933. He is one of three surviving sons, an older brother having died in childhood. (In Saville and In Celebration the death as a child of a mining family's eldest son has a powerful effect on the parents and some of the remaining brothers.) Although his father wanted his children to reach the middle class through education, Storey has indicated that this ambition was not pursued wholeheartedly.
Keywords: Storey, David, 1933- -- Criticism and interpretation.